APPLICATION OF THE МКS ЕN1317 ON THE ROADS OF THE REPUBLIC OF NORTH MACEDONIA - Ristov Riste; Ognjenovic Slobodan; Nedevska Ivana; Zafirovski Zlatko (Faculty of Technical Sciences Bitola, 2021)
The paper contains a comparison of the previous standard for use of elastic guardrail with the newly applied. The comparison will identify the advantages and disadvantages of both standards regarding the type of the materials, installation, designer approach and maintenance. In addition, comparison will be conducted regarding the safety aspect via constructed test sections.
Keywords: Disadvantages, Materials, Guardrail, Advantages, Comparison.